Capacidade de Retenção de Fósforo e Material Particulado em Suspensão por Manguezal de Área Impactada por Efluentes da Carcinicultura - Fonseca, Louize Viveiro da (2009)
The mangrove forests stabilize the coastal erosion zone and act as a buffering between the continent and the sea. This forest presents high resilient degree, suggested to be used as marker of environmental changes. They play an important role in the energy flow and nutrients cycles. They are suffering with the growth of shrimp ponds. This tends to be responsible of causing serious environmental impacts, particularly in the northeast of Brazil and being associated with the emission of solids in suspension and nutrient in estuaries. The mangroves growth has a retention capacity capable to minimize the impact of the effluents that can be distinguished between areas being recognized contaminated and areas with natural characteristics, for that we were intended to test this capacity through the study of phosphorus and TSS mass balance in these estuaries. Sampling of water and sediment was in 2 campaigns: in the Jaguaribe creek (impacted) and in the Pacoti creek (natural) at tidal cycle. The parameters pH, OD, %OD, T, salinity and cond were measured in situ with portable multimode. TSS was obtained by gravimetric method (APHA, 2001). The fractions of phosphorus in water and in sediments were according to the Grasshoff et al. (1999). The TP extraction in sediment followed Berner & Rao (1994). The flow measures were calculated according to OVALLE et al (1990) and the estimate of the mass balance was obtained in simplified ways starting from the mass between the entrance processes to the agreement with the tide change. The hydrochemistry parameters showed the same for the two study areas, except for OD, that reached suboxic values for Jaguaribe creek. TSS varied between 23,1 and 172,9 mg.L-1 for two campaigns in the Jaguaribe creek and 23,5 and 97,7 mg.L-1 for the Pacoti creek, having been considered acceptable when compared the other works. The phosphate concentrations for Jaguaribe creek varied for D-PO4 between 2,1 and 6,5 μM in Jaguaribe creek, and 0,1 and 0,9 μM in Pacoti creek; for T-PO4 between 3,2 and 15,9 μM for Jaguaribe creek and 2,9 to 7,3 μM for Pacoti creek; and for Part-PO4, between 1,3 and 11,9 μM for Jaguaribe creek and 2,8 to 7,7 μM for Pacoti creek; tends Jaguaribe presented larger concentrations that Pacoti in all the campaigns and fractions, probably due to the effluents of shrimp pond. The phosphorus in the sediment varied from 180,6 to 224,9 μg of P/g for TP in Jaguaribe creek and in Pacoti creek it was of 117,5 μg of P/g, showing that the largest concentrations of P in the sediment happened in Jaguaribe. The flows of TSS (Flx TSS) varied from 0 to 184,5 g.s-1, in the first campaign in Jaguaribe creek, 0 to 36,4 g.s-1, in Pacoti creek and between 0 and 836,5 g.s-1 in the second campaign of Jaguaribe, where the values were almost an order of greatness larger than in the previous and your behavior was more accentuated during the ebb tide. Flx D-PO4 in Jaguaribe creek varied from 0 to 709 mg.s-1 and 0 to 9.113 mg.s-1, while in Pacoti creek it varied from 0 to 13,4 mg.s-1. To Flx T-PO4, variation was observed from 0 to 1.248 mg.s-1 and from 0 to 11.065 mg.s-1 in Jaguaribe creek, and from 0 to 295 mg.s-1 in Pacoti creek, and Flx Part-PO4 varied from 0 to 539 mg.s-1 and from 0 to 3.471 mg.s-1 for the campaigns of Jaguaribe, and from 0 to 281 mg.s-1 for Pacoti creek. The fluxes of the fractions of P and of TSS are much related with current speed. The estimates of mass balance showed that the river Jaguaribe retains the phosphorus fractions as much as the TSS, corroborating with the hypothesis generated by this work. However, their support capacity it is reduced in comparison with the balance results found for the river Pacoti that presented retention of materials much more significant than the creek in Jaguaribe River, characterizing him with a great support capacity. However, Jaguaribe River can probably be entering in an accelerated process of aging caused by the antrophic actions that impacts in its waters.